e-Census Based Decision Making for Employment Planning - Dutta, Ajay; Syamala Devi, M; Arora, Manish (International Journal of Computer Sciences and Engineering, 2018)
e-Governance refers to the delivery of government information and services using Information and Communications Technology (ICT) to citizens or businesses or government. Census is a government activity of citizen socio-economic data collection process for the preparation of the citizen database. Census data is used for various activities planning like increasing literacy rate, removal of unemployment and healthcare issues etc. The aim of the paper is to present web based spatial dimensional modeling of the job seekers for assisting in taking high level decisions for government institutions like National Institution for Transforming India (NITI) Aayog and State Governments etc. The proposed system employs Online Analytical Processing (OLAP) and Data mining techniques for finding the job seeker population correlations among multiple fields like gender, the age structure of the population, geographical area and educational qualification in census database. OLAP techniques like roll-up, drill-down, slice and dice are implemented for dimensional modeling of the proposed system. Microsoft Visual Studio is used as an integrated environment for prototype development of a web based application with c# as the programming language. Microsoft SQL server is used as a backend relational database management system. It is concluded that the census database can be effective and efficient in achieving sustainable development goals of government as it can provide accurate and timely information within a reasonable amount of time.